Bat Intelligence For Tunning Power System Stabilizer At Barru Power Plant - Muhammad Ruswandi Djalal; Andareas Pangkung; Sonong Sonong; Apollo Apollo (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2018)
Changes in load on the power system suddenly, can cause dynamic disruption. This disturbance can not be responded well by the generator, so it can affect the system dynamic stability, such as the occurrence of oscillation speed and rotor angle. Conventional control of excitation and governor, also unable to repair the oscillations, so that additional controllers such as Power System Stabilizer (PSS) are required. In the use of PSS, there are several problems that often arise, namely the correct tuning of PSS parameters. In this research, we proposed a method of smart computing based on bat algorithm, for tuning PSS parameters. From the analysis results can be concluded, the performance performance of generator barru increased with the installation of Power System Stabilizer with optimal PSS parameter, with parameters respectively Kpss = 44.0828, T1 = 0.0284, T2 = 0.0146, T3 = 0.7818, T4 = 1.2816.